Surgical management of recurrent disc herniations with microdiscectomy and long-term results on life quality: Detailed analysis of 70 cases - Albayrak, Serdal; Ozturk, Sait; Durdag, Emre; Ayden, Omer (Medknow Publications & Media Pvt Ltd, 2016)
Background: Aim of this paper is to recall the surgical technique used in the recurrent lumbar disc herniations (LDHs) and to share our experiences. Materials and Methods: Out of series of 1115 patients who underwent operations for LDH between 2006 and 2013, 70 patients underwent re-operations, which were included in this study. During surgery, lateral decompression performed over the medial facet joint to the superior facet joint border was seen after widening the laminectomy defect, and microdiscectomy was performed. The demographic findings of the patients, their complaints in admission to hospital, the level of operation, the condition of dural injury, the first admission in the prospective analysis, and their quality of life were evaluated through the Oswestry scoring during their postoperative 1st, 3rd, 6th-month and 1st, 3rd, 5th and 7th-year follow-up. In the statical analysis, Friedman test was performed for the comparison of the Oswestry scores and Siegel Castellan test was used for the paired nonparametrical data. A P < 0.05 was considered statistically significant. Results: Considering the Oswestry Index during the follow-ups, the values in the postoperative early period and follow-ups were seen to be significantly lower than those at the time of admission to hospital (P < 0.05). None of the patients, who re-operated by microdiscectomy, presented with iatrogenic instability in 7 years follow-up period. Conclusion: Microdiscectomy performed through a proper technique in the re-operation of recurrent disc herniations eases complaints and improves the quality of life. Long-term follow-ups are required for more accurate results.
Keywords: Disc herniation; life quality; microdiscectomy; oswestry index; recurrence